Sample sizes for time-to-event endpoints: should you insure against chance variations in accrual? - Abel, Ulrich; Jensen, Katrin; Karapanagiotou-Schenkel, Irini (Contemporary clinical trials, 2012)
This note addresses the questions of whether one should safeguard against a potential loss of power due to random variations of the accrual time, how this “insurance” can be formulated, and how much the sample size needs to be increased to obtain it.
Available online 9 November 2011
Gesehen am 30.11.2018